The association between the north Indian Ocean and summer monsoon rainfall over India - SINGH, O. P. (MAUSAM, 1998)
Utilizing the marine meteorological data of the period 1961-81, the sea level pressure (SLP) and sea surface temperature (SST) distributions have been obtained on a 5° grid-mesh over the north Indian Ocean area bounded by 0°- 25°N, 50°- l00°E for each individual year. It has been found that the SLP and SST fields for the month of May provide predictive indications of subsequent summer monsoon rainfall over India. Significant negative correlations have been found between the mean SLPs of May over the latitudinal belts 5°-10°, 10°- 15°, 15°-20° and 20°-25°N of Arabian Sea and Bay of Bengal and all India rainfall departures of succeeding summer monsoon season. The mean SST gradient over the Arabian Sea between 7.5°- 17 .5°N during May has been found to have significant positive correlation with all India rainfall of subsequent monsoon. The study suggests that certain functions of SLP and SST of May over the north Indian Ocean can prove to be useful predictors for subsequent summer monsoon rainfall over India.